THE RELATIONSHIP BETWEEN LOW BIRTH WEIGHT AND THE INCIDENCE OF ASPHYXIA AT KRAMAT JATI HOSPITAL YEAR 2023 - Rohmat, Liza Azizah; Cusmarih, Ns. (HEARTY, 2025)
Because the global infant mortality rate serves as a benchmark for a country's health, infant mortality remains a serious problem. Based on existing statistics, Africa has the highest incidence of newborn deaths, namely 39.6%, followed by Asia at 39.4%. to determine the relationship between low birth weight and the frequency of asphyxia at Kramat Jati District Hospital in 2023. This research is quantitative and uses case control methodology and correlation methods. The sample in this study consisted of 312 respondents, 156 of whom were LBW newborns and 156 of whom suffered from asphyxia. Kramat Jati Regional Hospital's medical record files were used as a research tool in this study. Univariate and bivariate data analysis was used. Research findings showed that 156 (or 50%) respondents were underweight at birth. 156 people, or 50% of the sample, reported suffering from asphyxia. With a p value of 0.003, the results of bivariate analysis show that there is a relationship between low body weight and the occurrence of hypoxia at Kramat Jati Regional Hospital. By further honing skills and abilities in providing client health services, nurses can prevent pregnancies with low birth weight babies by monitoring and providing prenatal care. They can also treat neonates and detect complications of pregnancy and childbirth early, because this is one of the factors that causes newborns to experience asphyxia.